Reproducibility of coffee quality cupping scores delivered by cupping centers in Ethiopia. Issue 5 (19th August 2016) - Worku, Mohammed; Duchateau, Luc; Boeckx, Pascal
Abstract: The reproducibility of cupping scores for 30 coffee samples from eastern, southern and southwestern origins in Ethiopia was evaluated by comparing absolute differences within and between nine cuppers, three Ethiopia Commodity Exchange (ECX) cupping centers (Jimma, Awassa, Dire Dawa) and three coffee origins. Additionally, the correlation between cupping scores of an exporter (ECX) and an importer (EFICO Agency SA) was evaluated based on 70 coffee samples from five different origins. Differences in ECX cupping score variability were generally observed for all studied quality attributes. Variability was higher between than within cuppers. Furthermore, particular high variable scores were observed for the Dire Dawa cupping center and for some attributes of the southwestern coffee origin. However, the average absolute difference for total cup quality was small (ca. 3 on a 100 scale), which indicates that cupping scores by the ECX are sufficiently reproducible to allow reliable coffee quality grading. However, no correlation was observed between cupping scores of the exporter and importer, which indicates a lack of interchangeability between grading data produced by both actors. Practical applications: Testing and grading of the quality of green coffee beans by the Ethiopia Commodity Exchange cupping centers is fairly reliable. However, the exporter quality scores and grades can most likely not be used interchangeably with those of an importer.